Performance analysis of the start phase of skeleton athletes at international competitions - Oguchi, T.; Yamamoto, J.; Yamaguchi, Y.; Schwameder, H.; Ae, M. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of this study was to investigate characteristics of the skeleton start motion from the viewpoint of step frequency and step length. Twenty-six male and twenty female skeleton athletes at international competitions were videotaped and analysed their start motion with the three-dimensional DLT method. There were high significant correlations between the start time and the goal time in both men (r = 0.947, p < 0.001) and women (r = 0.741, p < 0.001). As for the start time, men showed a significant correlation with the step length at the 1st step (r = -0.606, p < 0.01) while women showed significant correlations with the step frequency at the 1st (r = -0.475, p < 0.05), 3rd (r = -0.497, p < 0.05) and 5th (r = -0.471, p < 0.05) step. These result indicated that men emphasized step length at the 1st step, while women relied more on step frequency.